The epidemiology of traumatic brain Injury due to traffic accidents in Latin America: a narrative review (2020)
ObjectiveTraumatic brain injuries (TBIs) are devastating injuries and represent a major cause of morbidity and mortality worldwide. Traffic accidents are one of the main causes, especially in low- and middle-income countries. The epidemiology of TBI due to road traffic in Latin America is not clearly documented.MethodsA narrative review was conducted using PubMed, SCOPUS, and Google Scholar, looking for TBI studies in Latin America published between 2000 and 2018. Seventeen studies were found that met the inclusion and exclusion criteria.Results It was found that TBI due to road traffic accidents (RTAs) is more frequent in males between the ages of 15 and 35 years, and patients in motor vehicles accounted for most cases, followed by pedestrians, motorcyclists, and cyclists.ConclusionRoad traffic accidents is a common cause of TBI in Latin America. More studies and registries are needed to properly document the epidemiological profiles of TBI related to RTAs.